2006
DOI: 10.1002/ardp.200500168
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Potent Antimicrobial Activities of Some Novel Retinoidal Monocationic Benzimidazoles

Abstract: Several 2-(5,5,8,8-tetramethyl-5,6,7,8-tetrahydronaphthalen-2-yl)-1H-benzimidazole-5-carboxamidine analogues were synthesized for their antibacterial and antifungal activities against S. aureus, Methicillin-resistant S. aureus (MRSA), C. albicans, and C. krusei. MIC values of the targeted compounds 43-58 are comparable to those of Fluconazole and Sultamicillin. The most potent compounds, 51 and 53, showed MIC values as 0.78 and 1.56 microg/mL against S. aureus and C. albicans, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…All new compounds were confirmed by 1 H-NMR, 13 C-NMR, COSY, HSQC, HMBC, LC-MS, and elemental analyze data. The in vitro antistaphylococcal activity revealed that all the carboxamidines showed moderate to potent inhibitory activity, against S. aureus and methicillin-resistant S. aureus (MRSA) strains and compound 28 displayed close activity to the reference clinical drugs.…”
Section: Resultsmentioning
confidence: 75%
“…All new compounds were confirmed by 1 H-NMR, 13 C-NMR, COSY, HSQC, HMBC, LC-MS, and elemental analyze data. The in vitro antistaphylococcal activity revealed that all the carboxamidines showed moderate to potent inhibitory activity, against S. aureus and methicillin-resistant S. aureus (MRSA) strains and compound 28 displayed close activity to the reference clinical drugs.…”
Section: Resultsmentioning
confidence: 75%
“…[ 26–28 ] Many studies have supported the antimicrobial effect of a naphthalene ring on bacterial and fungal strains. [ 29–31 ] In fact, several naphthalene‐containing drugs such as nafcillin, naftifine, tolnaftate, and terbinafine are currently available to treat microbial infections (Figure 1). Naphthalene derivatives bearing a functional group, especially an ‐OH group, on α and β positions possess very good antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…The facts that benzimidazole nuclei is very important pharmacophore in modern drug discovery as well as in medicinal chemistry and that benzimidazole residue is a constituent of vitamin B12, support their potential use as therapeutics. Therefore, benzimidazoles display diverse biological activities such as antimicroabial [19,20], antifungal [21], antitumor [22e24], antiviral [25,26], antihistaminic [27] etc. Benzimidazole and its derivatives have additionally found applications in several other areas as optical laser and polymer dyes in optoelectronics [28,29], organic luminophores, fluorescent tags for detection of biological important molecules, as DNA, RNA or proteins and enzymes [24,30] etc.…”
Section: Introductionmentioning
confidence: 99%